Metamorfosa Radikalisme pada Lembaga Pendidikan di Sulawesi Tenggara - La Ode Abdul Wahab (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Research on the metamorphosis of radicalism in educational institutions in Southeast Sulawesi has been conducted and focused on the segregation potential to be a radical individuals and groups to preach, especially in educational institutions in the Southeast Sulawesi. Data obtained through questionnaires, structured interviews, observation, document tracking and focus group discussion.The results showed that the metamorphosis of radicalism on the knot of educational institutions in Southeast Sulawesi spreading through the penetration movement in educational institutions such as on college campuses and in schools, especially in public campuses with the goal of lecturers and students and public schools targeted teachers and students. The spread on campus through student propaganda agency involving senior students and in the school and through extra-curricular involving senior students with methods of brainwashing. Lecturer plays an important role in the growth of radicalism as teachers and leaders of radical organizations with a method of indoctrination while teachers act through the hidden curriculum. The policy of the state budget subsidies to student organizations affiliated to the radical organization helped sustain the growth of radicalism on campus.The study recommends that efforts to break the chain of radicalism in educational institutions in Southeast Sulawesi can be done by educators either individually or as an educator together with government